Art for Well-being: Insights into Early Childhood Education in Slovenia and Iceland - Štirn Janota, Petra; Dýrfjörð, Kristín (Revija za elementarno izobraževanje, 2025)
In this article, we explore how arts education promotes well-being in preschool education by comparing the views of Slovenian and Icelandic educators and students. In Slovenia, a structured curriculum approach predominates, while in Iceland creativity, learning in nature and finding solutions in an open learning environment are emphasised. Both approaches promote emotional expression, ethical awareness, and sustainable education. We highlight the challenges in teacher training and emphasise the need for training and inclusion of pedagogical practises in the arts in relation to health and well-being, while also demonstrating the importance of the arts experience for the health and well-being of both educators and preschool students.
Keywords: cultural and arts education, health, preschool education, well-being, preschool teacher education.